Articulate Storyline Learning Media on Speed and Discharge Concepts for Elementary School - Ramadhanti, Salzhabila; Kusmaharti, Dian; Yustitia, Via (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The low level of understanding among fifth-grade students in learning the concepts of speed and discharge causes difficulties in solving story problems. This research aims to develop a learning media using an Articulate Storyline for the concepts of speed and discharge in the fifth grade of SDN Krian IV. The Articulate Storyline learning media contains concepts of speed and discharge presented in a narrative form, accompanied by triggering questions and interactive quizzes. The Research and Development method with the 4D model was used, but only up to three stages: Define, Design, and Development. Time constraints were a consideration for the researcher in determining the research stages. Data collection techniques used in this research included interviews with fifth-grade teachers and questionnaires for validation. The research results are as follows: 1) the development process of Articulate Storyline learning media for the topics of speed and discharge went through several stages and product revisions; 2) the Articulate Storyline learning media for the concepts of speed and discharge meets the criteria for suitability to be used in the learning process, as indicated by the validation results from an expert in three aspects: media, content, and language assessment, all of which received the category of Very Feasible.